CHALLENGES FOR DEVELOPING TEACHER COMPETENCIES IN THE CONCENT ERA - Oktarina, Wulan; Lestari, Citra; Annur, Saipul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Teachers have very important responsibilities in their role as educators in schools. Achieving quality learning goals requires continuous improvement of teacher competence as time goes by. This writing aims to discuss and understand the challenges of developing teacher competency in learning in the contemporary era. This research uses qualitative methods in the form of a literature study, with a descriptive approach. Data was collected through references from books and literature related to the challenges of developing teacher competency in learning in the contemporary era. The research results show that teacher competency is the ability possessed by teachers and includes aspects such as knowledge, skills, thought processes, personal adaptation, attitudes and values that they apply in teaching practice. There are four abilities that teachers need: educational abilities, personality abilities, social abilities, and professional abilities. In addition, teacher skills development faces various challenges, including legislative, socio-cultural, technological and political challenges.